Data Acquisition System Design of Length Gauge - Ocka Hedrony; Bernadus H. S; Adindra Vickar Ega; Ghufron Zaid; Sastra Kusumawijaya (Instrumentasi, 2018)
Length gauge is one of measurement standard in the Length Metrology Laboratory, Research Center Metrology – LIPI. Practical use and good accuracy make it a mainstay in calibration. In use, length gauge requires a display unit to display readings of measuring results. The display unit is very susceptible to damage because it is directly connected to an electric power supply. To procure the display unit, requires funds and time. Therefore, the objective of the research is to design a length gauge data acquisition system that is simple and low cost without compromising function. Research was carried out by making a current into a voltage converter, converting an analog voltage signal into a pulse signal, separates the signal when the length gauge moves up and down, counting the generated pulse signal and displays it on the PC. Once the data acquisition system is calibrated, it was found that the readability of the system is 2 μm and with an uncertainty of 2.0 m. With this value of this uncertainty, based on ANSI/NCSL Z540-1-1994, the data acquisition system can be used as standard to calibrate measuring devices with an accuracy of at least 8 m.